A suggested framework for integrated reporting contribution to enhancing sustainable performance: an applied study at the Elaf Islamic private Bank - Kazem, Zahraa Kareem; Noorullah, Alaa Shamsallah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to shed light on the contribution of integrated reports in promoting sustainable performance, where integrated reports will be addressed in terms of its concept and importance to economic units and their users and objectives and the most important guidelines and elements contained in the report, and then to identify the concept of sustainable performance (SP) in addition to the three most important pillars of sustainability which are the environmental, social and economic dimensions. however. In order to reach the objectives of the study, this study was divided into several axes where the first axis was devoted to the concept of integrated reports , and the second axis was devoted to the definition of sustainable performance (SP), while the third axis is related to the practical aspect, and finally, the study presents the most important conclusions and recommendations it reached.